The interrelationships between bank risk and charter value in ASIAN-5 - Nguyen Dat; Tu Dq Le (Journal of Applied Economics, 2022)
This study examines the interrelationships between bank risk and charter value in five countries in Southeast Asia (ASEAN-5) from 2006 to 2019 using a simultaneous equations model. The findings show a two-way relationship between bank risk and charter value. More specifically, the positive relationship between charter value and bank risk implies that banks with a more excellent charter value tend to pursue fast growth strategies and thus may face a higher risk. This positive link, however, only holds up to a certain level of charter value. On the other hand, the negative impact of bank risk on charter value argues that more risky banks tend to generate lower returns, thus reducing charter value. Additionally, a bidirectional relationship between them still holds when using an alternative measure of bank risk and controlling for the global financial crisis and governance indicators. Therefore, our findings provide critical implications for policymakers, managers, and academics.
Keywords: 330; 3SLS; ASEAN-5; Bank risk-taking; charter value; SEM